Transforming Tourism MSMEs Based on a Green Economy Towards a Sustainable Economy - Panji Rizki Kurniawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the transformation of tourism MSMEs based on green economy towards sustainable economic development in Indonesia. Using a literature review method, this research examines various scientific sources published in the last ten years regarding green economy practices in tourism MSMEs. The results show that the transformation of tourism MSMEs towards a green economy can be achieved through four main pillars: adoption of environmentally friendly technology, development of green products and services, capacity building of human resources, and support from government policies. The main challenges faced include limited capital, lack of knowledge about green practices, and weak market access. However, the implementation of green economy principles provides significant benefits including operational cost efficiency, increased competitiveness, and positive contributions to environmental preservation. This study concludes that successful transformation requires synergy between MSMEs, government, academia, and society to create a sustainable tourism ecosystem.